Topical and Methodological Trends in ELT Research of English Education Students at Universitas Negeri Semarang - Akhmad Yani; Mursid Saleh (English Education Journal, 2022)
This study explores some students’ output in doing the research articles according to their trends in topics and methodology. Therefore, this research aimed at finding out the tendency and less frequency research topics interest of English Education students at UNNES Graduate. Theoretically, both topical and methodological issue in accomplishing the academic research were significantly considered as they offerred the study credibility and yields reliable scientific results. Additionally, they also offerred a thorough plan that aids in keeping researchers on course, facilitating a simple, efficient, and manageable approach (Fraenkel and Wallen, 2009; Richard and Rodgers, 2014). The research design of this study was longitudinal . survey design proposed by Creswell (2012) The sample of the survey was English Education students’ papers at UNNES Graduate School in the period of 2016-2021 and they were 77 students. Data collection technique was both survet and questionnaire. The study found that topic about English Language Teaching, literature, and translation as the existing individual interest were become the tendency in present period. Topics related to teaching strategies, teaching media, L2 remote learning challenges and opportunities, L2 emergency curriculum, L2 skills development, technology as well as assessment become the generate situational interest due to the covid-19 Post-Pandemic era. The study concluded that forty-four of seventy-seven students have awareness on including remote learning environment-related topics in future research and they need some professional development on integrating remote learning environment issues into their research. For the further study, the writers hopefully can explore about the implementation of students situational interest by enhancing students’ performance in national conference such as students conference using Research-Based Learning via online training. The goal of this study was supportive to be reflected in the issue of English educational development such providing the further writers to be aware with the set of writing organization technique to complete the academic papers.